Study of the accessibility diagnosis on the public higher institutions website in Malaysia - Abuaddous, Hayfa Yousef; Jali, M.Z.; Basir, Nurlida (2013)
University web pages play a central role in the activities of all students.In order to assess the current state of university web site accessibility, we performed an automated evaluation of the home pages of 20 Public Higher Educational Institutions of Malaysia. Two experiments were made in 2012 and 2013 to see if there is a significant change in the results.Three Online Automated tools were used along the two experiments to see the differences between numbers of accessibility issues discovered by each tool.The results showed significant issues and no big improvements have been made to the websites from 2012 to 2013.